Gut Microbiota—A Future Therapeutic Target for People with Non-Alcoholic Fatty Liver Disease: A Systematic Review - Forlano,R; Sivakumar,M; Mullish,BH; Manousou,P (International Journal of Molecular Sciences, 2022)
Non-alcoholic fatty liver disease (NAFLD) represents an increasing cause of liver disease, affecting one-third of the population worldwide. Despite many medications being in the pipeline to treat the condition, there is still no pharmaceutical agent licensed to treat the disease. As intestinal bacteria play a crucial role in the pathogenesis and progression of liver damage in patients with NAFLD, it has been suggested that manipulating the microbiome may represent a therapeutical option. In this review, we summarise the latest evidence supporting the manipulation of the intestinal microbiome as a potential therapy for treating liver disease in patients with NAFLD.